Ceriantheomorphe brasiliensis (Cnidaria Ceriantharia): how does it behave? - Ceriello, Hellen [UNESP]; Stampar, Sérgio N. [UNESP] (Taylor & Francis, 2023)
Behaviour research on Cnidaria, particularly Ceriantharia (Cnidaria, Anthozoa), is generally uncommon. Although ceriantharians or tube-dwelling anemones are known to build soft tubes, their tube-building behaviours remain unknown. In this study, we describe for the first time the tube-building behaviour of Ceriantheomorphe brasiliensis and detail its behaviour in natural habitat, including illustrations and videos of live specimens. Our results showed that C. brasiliensis can build more than one tube throughout its life, the tubes are usually ‘L-shaped’, longer than the polyp, and vertically oriented when built in deeper substrates, but horizontally oriented when built in shallower substrates. During tube construction, the polyp does not feed or use its tentacles to catch or select specific sediment particle sizes for tube construction. Given the vertical orientation of the tube, it is possible that the tube-building behaviour of C. brasiliensis differs from that of other species. Although this study only included a single specimen, the behaviours observed were constantly repeated by the animal in every test, from the first trial to the last, suggesting that they can occur on occasion. Furthermore, this research contains useful information that may guide future studies of tube-building behaviour in Ceriantharia which are, currently, non-existent.
Keywords: Anthozoa; behaviour; bioconstruction; tube-building; tube-dwelling anemone